Karakteristik Bakteri Streptococcus agalactiae NP104O, S01-196-16 dan NMbO Penyebab Streptococcosis pada Ikan Nila (Oreochromis niloticus) - Achmad Suhermanto; Herdianto T; Suhermin; Ridwan; Nurmawanti I (Jurnal Airaha, 2019)
Failure of tilapia culture in Indonesia in the hatchery, nursery and rearing segments mostly is caused by Streptococcus agalactiae infection. This study aimed to detect the characteristics of bacteria S. agalactiae NP104O, S01-196-16 and NMbO which infect tilapia in aquaculture. Bacterial isolation was carried out during an outbreak of streptococcosis, further analysis based on morphological and biochemical characters. The pathogenicity test was done by injecting bacteria intraperitoneally at a dose of 107 CFU fish-1. The results showed that all isolates was cocci, gram positive, negative catalase and negative oxidase. The three isolates had different concentrations and growth patterns until end of the observation. Pathogenicity test results obtained all fish injected with NP104O, S01-196-16 and NMbO bacteria appeared as clinical symptoms of melanosis, unilateral or bilateral exophthalmos, turbidity in the eye, curved vertebrae forming the letter C, erratic, and whirling. Hopefully, the results of this study can be used as a reference for prevention of streptococcosis infections in tilapia.